Prevalence of Gastrointestinal Parasites in Cattle Calves in and around Rewa, Madhya Pradesh - Telu, Naveen; Dixit, Pooja; Dixit, Alok Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted to know the prevalence of gastrointestinal parasite infection in cattle calves in and around Rewa, Madhya Pradesh. The study revealed that overall prevalence of gastrointestinal parasite infection was 29.04% (97/334). The highest prevalence was of coccidia infection (11.98%) and least of Toxocara vitulorum (0.30%) and Fasciola gigantica (0.30%). In post-monsoon season, the prevalence of parasite infection was significantly higher. Key words: Cattle calves, Coccidia, Gastrointestinal Parasites, Nematodes, Prevalence.